The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2174/138920106779116874
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Linolenic Acid: An Antiinflammatory Omega-6 Fatty Acid

Abstract: Inflammation plays an important role in health and disease. Most of the chronic diseases of modern society, including cancer, diabetes, heart disease, arthritis, Alzheimer's disease, etc. have inflammatory component. At the same time, the link between diet and disease is also being recognized. Amongst dietary constituents, fat has gained most recognition in affecting health. Saturated and trans fatty acids have been implicated in obesity, heart disease, diabetes and cancer while polyunsaturated fatty acids (PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
160
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(187 citation statements)
references
References 43 publications
2
160
1
6
Order By: Relevance
“…It would be desirable to enrich dairy products with polyunsaturated fatty acids, which are not synthesized in the human body, and the intake of which from food is often very poor. These acids have many health-promoting properties (Delgado-Lista et al, 2012;Kapoor and Huang, 2006;Ranieri et al, 2009). High levels of interest in the consumption of omega 3 fatty acids have made it possible to produce food fortified with EPA and DHA from marine sources (Kolanowski and Weiβbrodt, 2007;Rognlien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It would be desirable to enrich dairy products with polyunsaturated fatty acids, which are not synthesized in the human body, and the intake of which from food is often very poor. These acids have many health-promoting properties (Delgado-Lista et al, 2012;Kapoor and Huang, 2006;Ranieri et al, 2009). High levels of interest in the consumption of omega 3 fatty acids have made it possible to produce food fortified with EPA and DHA from marine sources (Kolanowski and Weiβbrodt, 2007;Rognlien et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-linolenic acid is of particular interest owing to its anti-inflammatory [13] and anticancer property [14]. Besides this, it is used in the treatment of multiple sclerosis [15] and rheumatoid arthritis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The role of GLA in metabolism is various; dihomo-γ-linolenic acid (DGLA) is the active form of GLA that mediates most of its physiological actions including cell to cell communication, synthesis of prostagladins, anti-inflammatory, vasodilatory and anti-aggregatory actions (3). However, it has been found that in vivo conversion of linolenic acid into GLA is hindered by ageing, consumption of alcohol and vitamin deficiency (4).…”
Section: Introductionmentioning
confidence: 99%